Aptamer-Based Fluorescence Quenching Approach for Detection of Aflatoxin M1 in Milk - Qiao, Qinqin; Guo, Xiaodong; Wen, Fang; Chen, Lu; Xu, Qingbiao; Zheng, Nan; Cheng, Jianbo; Xue, Xiuheng; Wang, Jiaqi (Frontiers in Chemistry, 2021)
Aflatoxin M1 (AFM1), one of the most toxic mycotoxins, is a feed and food contaminant of global concern. In this study, we developed a fast and simple method for detection of AFM1 based on a structure-switching signaling aptamer. This aptasensor is based on the change in fluorescence signal due to formation of an AFM1/aptamer complex. To generate the aptasensor, the specific aptamer was modified with FAM (carboxyfluorescein), and their complementary DNAs (cDNA) were modified with a carboxytetramethylrhodamine (TAMRA) quenching group. In the absence of AFM1, the aptamers were hybridized with cDNA, resulting in quenching of the aptamer fluorescence due to the proximity of the aptamer’s fluorophore to the quenching group on the cDNA. On the other hand, in the presence of AFM1, a structural switch in the aptamer was induced by formation of an AFM1/aptamer complex. Changes in the structure of the aptamer led to the release of the cDNA, causing the generation of a fluorescence signal. Thus, AFM1 concentrations could be quantitatively monitored based on the changes in fluorescences. Under optimized conditions, this assay exhibited a linear response to AFM1 in the range of 1–100 ng/mL and a limit of detection of 0.5 ng/mL was calculated. This proposed aptasensor was applied to milk samples spiked with a dilution series of AFM1, yielding satisfactory recoveries from 93.4% to 101.3%. These results demonstrated that this detection technique could be useful for high-throughput and quantitative determination of mycotoxin levels in milk and dairy products.